UJI LARVASIDA NYAMUK (Aedes aegypti) DARI ASCIDIAN (Didemnum molle) - Rumengan, Antonius P (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
Dengue haemorrhagie fever is one of the disease which caused by dengue virus. It spreads out by mosquito Aedes aegypti as the vector. To date, people use abate as the larvacidal.Â  Yet it causes the negative effects, such as bad odor, rustiness of the water container and resistency either to the larvae or to the living environment if continue using it. The objective of the research was to examine the larvacidal activity of Didemnum molle extract against A. aegypti larvae. The sample was extracted with methanol to give methanolic extract which was further partitioned with ethyl acetate, hexane, and chloroform to yield three fractions of ethyl acetate, hexane, and chloroform. Methanolic extract and the three fractions were tested against the A. aegypti larvae instar III for several concentrations. Abate and tap water were used as controls. The result exhibited that Didemnum molle extracts contain or produce larvacidae substances against A. aegypti larvae. They are approved by the data of methanolic extract and the 3 fractions which are more powerful than abate, particularly hexane. However it still needs to be purified to obtain single active compound.